Role of novel polysaccharide layers in assembly of the exosporium, the outermost protein layer of the Bacillus anthracis spore. Issue 3 (15th August 2022) - Lehmann, Dörte; Sladek, Margaret; Khemmani, Mark; Boone, Tyler J.; Rees, Eric; Driks, Adam
Abstract: A fundamental question in cell biology is how cells assemble their outer layers. The bacterial endospore is a well‐established model for cell layer assembly. However, the assembly of the exosporium, a complex protein shell comprising the outermost layer in the pathogen Bacillus anthracis, remains poorly understood. Exosporium assembly begins with the deposition of proteins at one side of the spore surface, followed by the progressive encirclement of the spore. We seek to resolve a major open question: the mechanism directing exosporium assembly to the spore, and then into a closed shell. We hypothesized that material directly underneath the exosporium (the interspace) directs exosporium assembly to the spore and drives encirclement. In support of this, we show that the interspace possesses at least two distinct layers of polysaccharide. Secondly, we show that putative polysaccharide biosynthetic genes are required for exosporium encirclement, suggesting a direct role for the interspace. These results not only significantly clarify the mechanism of assembly of the exosporium, an especially widespread bacterial outer layer, but also suggest a novel mechanism in which polysaccharide layers drive the assembly of a protein shell. Abstract : Polysaccharide has a previously unknown role in assembly of the exosporium, a protein‐shell outer layer in many Bacillus spores. Exosporium assembly begins with the deposition of an initial layer (yellow), connected to one side of the developing spore surface by polysaccharide (red) (a). Exosporium (green) continues to assemble around the spore, ultimately encircling it (c, d), while a second polysaccharide layer (blue) accumulates.